System dynamics in tourism planning and development - Sedarati, Pooyan (2020)
System dynamics (SD) is a method that has the ability to capture the dynamic behavior of a complex system over time. The tourism industry, due to the myriad of interactions among its sectors, can be considered as a complex system. Therefore, SD has drawn the attention of tourism researchers over the last two decades. The goal of this study is to assess the application of the SD method in planning and development of the tourism industry. For this purpose, a systematic literature review was performed and a set of 27 papers was selected. The analysis of the papers shows the applicability of the SD method to address a multitude of different problems. Overall, however, it can be concluded that whilst the SD method has shown considerable potential to provide tourism decision-makers and regulators with tools for strategic and operational policy development at many different levels of analysis, the number of applications in this sector is still limited. Therefore, it is recommended that the use of SD modeling in the tourism industry be extended in order to promote a holistic understanding of the complex issues faced by this industry and to assist in the development of more effective policies.